Perancangan Ulang Tata Letak Fasilitas Produksi Menggunakan Algoritma CORELAP dan CRAFT pada CV CTR - Dony Sastra Danuatmaja; Oktavian Endiyansyah; Fadly Rizky Dermawan; Tiaradia Ihsan (SENTRI: Jurnal Riset Ilmiah, 2026)
In the Indonesian manufacturing industry, production efficiency is a key factor in improving company competitiveness, as a significant portion of operational costs originates from material handling activities. Inefficient facility layouts often result in long material flow distances, increased processing time, and high material handling costs. This study aims to optimize the facility layout of CV CTR, a manufacturing company producing ropes and threads, which currently experiences inefficient material flow due to improper departmental arrangement. The research applies a combination of the CORELAP (Computerized Relationship Layout Planning) algorithm and the CRAFT (Computerized Relative Allocation of Facilities Technique) method. CORELAP is used to construct an initial layout based on departmental closeness relationships, while CRAFT is employed to refine the layout through iterative department exchanges to minimize material handling costs. The results indicate that the proposed layout reduces the total Material Handling Cost (MHC) from Rp912,346.84 per day to Rp692,819.43 per day, achieving a 24% reduction. This confirms that the integration of CORELAP and CRAFT effectively improves material flow efficiency and reduces operational costs.